Students’ Reasoning About Float, Suspend, and Sink: The Role of Newton's Laws - Luh Sukariasih; Sutopo; Handayanto, Supriyono Koes; Panre, Andi Marwanti (Universitas Negeri Semarang, 2024)
The phenomena of floating, suspending, and sinking have been studied by students from elementary school to university level. However, many students, even at the university level, still misuse their knowledge to solve problems related to these phenomena. This has been revealed by many previous researchers. Student errors are mainly caused by students tending to apply intuition-based spontaneous-reflective thinking patterns triggered by salient features that appear in the problem rather than thinking deeply and reflectively. This research aims to reveal students’ understanding and reasoning about floating, suspending, and sinking phenomena in more detail. This research was conducted on first-year students of the Department of Physics Education of Halu Oleo University Kendari, Southeast Sulawesi, with 31 participants. Data was obtained through a series of tests and interviews. The test was given in two stages, and two instruments were developed to reveal students’ reasoning skills through the answers they wrote. The first test used the five-block problem. The second test was developed based on the first test’s results, which consisted of four test items. Based on descriptive analysis, it is found that students still use incorrect reasoning in solving floating, suspending, and sinking phenomena even though they know various concepts related to these events verbally. In general, the errors shown are caused by students not being able to use the concept of Newton’s laws of motion in solving various problems in physics, especially in the phenomena of floating, suspending, and sinking. The data obtained is then used as a reference in designing learning activities, which are expected to help students understand floating, suspending, and sinking phenomena more comprehensively.